Influence of Time and Intensity of Pruning on Growth and Flowering Behaviour of Cut Rose - Adhikari, Deb Raj; Baral, D. R.; Gautam, D. M.; Pun, U. K. (Nepal Journal of Science and Technology, 2015)
A field investigation was carried out during July 2008 to April 2009 in a farmer’s field at Gunjanagar-5, Chitwan, Nepal to evaluate the influence of time and intensity of pruning on growth and flowering behaviour of cut rose cv. Super Tata (Rosa hybrida). The experiment was laid out in a completely randomized block design with nine treatment combinations and replicated thrice. The treatments comprised of three dates of pruning i.e. 30th July, 15th August and 30th August and three pruning intensities i.e. heavy (6 buds per plant), medium (12 buds per plant) and light (18 buds per plant). Both time and intensity of pruning significantly affected growth and yield attributing parameters. The plants pruned heavily on 30th July produced highest plant height, number, length and diameter of canes. Similarly, stem bud as well as floral initiation were also earlier as compared to other treatments. On the other hand, fresh and dry weight of leaf and leaf area index were highest from the plants pruned heavily on 15th August. Flower stem diameter was higher in July 30th pruned rose plants while, flower stem length was found longer (47.67 cm) in August 15th pruned ones. Heavily pruned plants produced earlier floral initiation (45.48 days). Flower stem length (50.33 cm) and diameter (0.60 cm), length (2.91 cm) and diameter (2.29 cm) of floral buds were found highest from heavily pruned plants. Number of flowers per plant was recorded higher (22) from earlier (30th July) and lightly pruned rose plants. The longest duration of flowering (212.8 days) was observed from earlier and heavily pruned (198.1 days) plants. Sequential pruning can produce rose flowers at desired time. DOI: http://dx.doi.org/10.3126/njst.v15i1.12004 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 7-12